2013
DOI: 10.1002/anie.201302727
|View full text |Cite
|
Sign up to set email alerts
|

Rigid DNA Beams for High‐Resolution Single‐Molecule Mechanics

Abstract: Bridging the gap: Rigid DNA linkers (blue, see picture) between microspheres (green) for high‐resolution single‐molecule mechanical experiments were constructed using DNA origami. The resulting DNA helical bundles greatly reduce the noise generated in studies of conformation changes using optical tweezers and were applied to study small DNA secondary structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 39 publications
8
113
0
2
Order By: Relevance
“…The 20-30% error predicted by the theory matches well with the error found empirically in previous work by Chang et al (14). Large bead-size or linker-stiffness increases may lead to larger artifacts, however, as noted previously (15)(16)(17)(18); this is unfortunate because stiff linkers in particular allow for easier reconstruction of free-energy profiles (10,11,24,25). Optimizing assay design for one purpose (e.g., landscape reconstruction) may thus degrade its suitability for others (e.g., measuring kinetic properties).…”
supporting
confidence: 85%
“…The 20-30% error predicted by the theory matches well with the error found empirically in previous work by Chang et al (14). Large bead-size or linker-stiffness increases may lead to larger artifacts, however, as noted previously (15)(16)(17)(18); this is unfortunate because stiff linkers in particular allow for easier reconstruction of free-energy profiles (10,11,24,25). Optimizing assay design for one purpose (e.g., landscape reconstruction) may thus degrade its suitability for others (e.g., measuring kinetic properties).…”
supporting
confidence: 85%
“…One way to increase handle stiffness is to use shorter handles (42). An alternative is to replace the handle material with something stiffer, as done by Pfitzner et al (96), who showed that using rigid DNA origami beams in place of the double-stranded DNA handles typically used in optical trapping experiments sharpened the distributions and improved the reconstruction.…”
Section: Landscape Reconstructions From Equilibrium Measurements Of Ementioning
confidence: 99%
“…For example, Kauert et al 46 measured the torsional persistence length of 4-helix and 6-helix bundles to be 390 nm and 530 nm, respectively; Plesa and co-workers 58 demonstrated that the bending stiffness of DNA origami nanoplates was critical to their functional ion conductance; and Pfitzner et al 59 exploited the stiffness of DNA origami beams to improve the resolution of force spec-troscopy experiments. For example, Kauert et al 46 measured the torsional persistence length of 4-helix and 6-helix bundles to be 390 nm and 530 nm, respectively; Plesa and co-workers 58 demonstrated that the bending stiffness of DNA origami nanoplates was critical to their functional ion conductance; and Pfitzner et al 59 exploited the stiffness of DNA origami beams to improve the resolution of force spec-troscopy experiments.…”
Section: Designing and Characterizing Mechanical Stiffness Of Dna Orimentioning
confidence: 99%